Interobserver reliability in musculoskeletal ultrasonography: results from a "Teach the Teachers" rheumatologist course. Issue 1 (7th June 2005) - Naredo, E; Möller, I; Moragues, C; de Agustín, J J; Scheel, A K; Grassi, W; de Miguel, E; Backhaus, M; Balint, P; Bruyn, G A W; D'Agostino, M A; Filippucci, E; et al.
Abstract : Objective: To assess the interobserver reliability of the main periarticular and intra-articular ultrasonographic pathologies and to establish the principal disagreements on scanning technique and diagnostic criteria between a group of experts in musculoskeletal ultrasonography. Methods: The shoulder, wrist/hand, ankle/foot, or knee of 24 patients with rheumatic diseases were evaluated by 23 musculoskeletal ultrasound experts from different European countries randomly assigned to six groups. The participants did not reach consensus on scanning method or diagnostic criteria before the investigation. They were unaware of the patients' clinical and imaging data. The experts from each group undertook a blinded ultrasound examination of the four anatomical regions. The ultrasound investigation included the presence/absence of joint effusion/synovitis, bony cortex abnormalities, tenosynovitis, tendon lesions, bursitis, and power Doppler signal. Afterwards they compared the ultrasound findings and re-examined the patients together while discussing their results. Results: Overall agreements were 91% for joint effusion/synovitis and tendon lesions, 87% for cortical abnormalities, 84% for tenosynovitis, 83.5% for bursitis, and 83% for power Doppler signal; κ values were good for the wrist/hand and knee (0.61 and 0.60) and fair for the shoulder and ankle/foot (0.50 and 0.54). The principal differences in scanning method and diagnostic criteria between experts were related to dynamic examination, definition of tendon lesions, and pathological v physiological fluid within joints, tendon sheaths, and bursae. Conclusions: Musculoskeletal ultrasound has a moderate to good interobserver reliability. Further consensus on standardisation of scanning technique and diagnostic criteria is necessary to improve musculoskeletal ultrasonography reproducibility.